Healthy, mtDNA-mutation free mesoangioblasts from mtDNA patients qualify for autologous therapy - Florence van Tienen; Ruby Zelissen; Erika Timmer; Marike van Gisbergen; Patrick Lindsey; Mattia Quattrocelli; Maurilio Sampaolesi; Elvira Mulder-den Hartog; Irenaeus de Coo; Hubert Smeets (Stem Cell Research & Therapy, 2019)
Abstract Background Myopathy and exercise intolerance are prominent clinical features in carriers of a point-mutation or large-scale deletion in the mitochondrial DNA (mtDNA). In the majority of patients, the mtDNA mutation is heteroplasmic with varying mutation loads between tissues of an individual. Exercise-induced muscle regeneration has been shown to be beneficial in some mtDNA mutation carriers, but is often not feasible for this patient group. In this study, we performed in vitro analysis of mesoangioblasts from mtDNA mutation carriers to assess their potential to be used as source for autologous myogenic cell therapy. Methods We assessed the heteroplasmy level of patient-derived mesoangioblasts, isolated from skeletal muscle of multiple carriers of different mtDNA point-mutations (n = 25). Mesoangioblast cultures with < 10% mtDNA mutation were further analyzed with respect to immunophenotype, proliferation capacity, in vitro myogenic differentiation potential, mitochondrial function, and mtDNA quantity. Results This study demonstrated that mesoangioblasts in half of the patients contained no or a very low mutation load (< 10%), despite a much higher mutation load in their skeletal muscle. Moreover, none of the large-scale mtDNA deletion carriers displayed the deletion in mesoangioblasts, despite high percentages in skeletal muscle. The mesoangioblasts with no or a very low mutation load (< 10%) displayed normal mitochondrial function, proliferative capacity, and myogenic differentiation capacity. Conclusions Our data demonstrates that in half of the mtDNA mutation carriers, their mesoangioblasts are (nearly) mutation free and can potentially be used as source for autologous cell therapy for generation of new muscle fibers without mtDNA mutation and normal mitochondrial function.